2008
DOI: 10.1097/hjh.0b013e3282f293c8
|View full text |Cite
|
Sign up to set email alerts
|

Forkhead class O transcription factor 3a activation and Sirtuin1 overexpression in the hypertrophied myocardium of the diabetic Goto-Kakizaki rat

Abstract: Diabetes-induced cardiac remodeling in Goto-Kakizaki rats is associated with cardiac hypertrophy, systolic dysfunction, increased apoptotic signaling and activation of the FOXO3a pathway. The present study also suggests that antiapoptotic Sirt1 protects against cardiomyocyte apoptosis and acts as a novel regulator of cardiomyocyte growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(41 citation statements)
references
References 56 publications
7
34
0
Order By: Relevance
“…This argument is in line with our echocardiographic data that show compensated heart in 1 mo STZ animals in terms of preserved cardiac function and unaltered SERCA2a expression in spite of high blood-glucose levels. In addition, two recent studies have also shown that cardiac SIRT1 expression is increased during compensatory cardiac hypertrophy of spontaneously diabetic Goto-Kakizaki rats and in spontaneously hypertensive rats (29,54). Based on these reports and findings of current investigations, we propose that a drop in cardiac expression of SIRT1 and subsequent loss of its deacetylase activity in advanced diabetes is likely the result of failure of this compensatory response, which then results in reduced SERCA2a expression and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 60%
“…This argument is in line with our echocardiographic data that show compensated heart in 1 mo STZ animals in terms of preserved cardiac function and unaltered SERCA2a expression in spite of high blood-glucose levels. In addition, two recent studies have also shown that cardiac SIRT1 expression is increased during compensatory cardiac hypertrophy of spontaneously diabetic Goto-Kakizaki rats and in spontaneously hypertensive rats (29,54). Based on these reports and findings of current investigations, we propose that a drop in cardiac expression of SIRT1 and subsequent loss of its deacetylase activity in advanced diabetes is likely the result of failure of this compensatory response, which then results in reduced SERCA2a expression and cardiac dysfunction.…”
Section: Discussionmentioning
confidence: 60%
“…28 Urinary albumin was measured by ELISA (Calltrend, Luckenwalde, Germany). Creatinine and electrolytes from serum and urine, as well as plasma lipids and liver enzymes, were measured by routine techniques.…”
Section: Cell-based and Chemical Studiesmentioning
confidence: 99%
“…Increased SIRT1 levels were found in hypertrophied and failing hearts [21,22]. Though cytoprotective, SIRT1 promotes cardiomyocyte growth under stress conditions, a study has found that blocking of SIRT1 activity with inhibitors increased the propensity of cardiomyocytes to death, but prevented hypertrophy of myocytes in response to stress stimuli.…”
Section: Protective Roles Of Sirt1 In Cardiovascular Diseasementioning
confidence: 95%